Konsep Pendidikan Islam Perspektif Kitab Muqaddimah Ibnu Khaldun - Bagas Mukti Nasrowi (Universitas Yudharta Pasuruan, 2017)
One of Islamic thinkers who are not a few of their work and thoughts and their existence in the scientific world, especially History and Philosophy, certainly has a connection with his thoughts on Islamic Education, although in a not large portion. That the style and thought of Science in the classical period, the middle period, until the modern period is always influenced by the bearer. From here comes a very varied thinking, along with thoughts that are not the same as its predecessor. Ibn Khaldun is a prominent figure in Islamic education. Ibn Khaldun's view of education, differs from Al-Ghazali's opinion in particular regarding the purpose of education. According to Al-Ghazali the aim of Islamic Education is only to get closer to God, while Ibn Khaldun argues that the goal of Islamic Education has been developed by obtaining good fortune.